Recent Advances in Nickel-Catalyzed Three-Component Difunctionalization of Unactivated Alkenes - Tu, Hai-Yong; Zhu, Shengqing; Qing, Feng-Ling; Chu, Lingling (Synthesis, 2020)
Catalytic, intermolecular difunctionalization of alkenes represents an efficient and diverse protocol for the buildup of molecular complexity from abundant materials by forging two chemical bonds in a single operation. Despite important progress in this area, transition-metal-catalyzed three-component difunctionalization of unactivated alkenes remains underdeveloped, mainly because of the low reactivity, reduced polarization, and high tendency toward β-hydride elimination of these compounds. In this context, nickel-catalyzed, selective, intermolecular difunctionalization methods that generally proceed via two distinct reaction pathways, migratory insertion of nickel species into alkenes and radical addition to alkenes, have been developed. This short review highlights recent advances in this area.1 Introduction2 Nickel-Catalyzed Three-Component Difunctionalization of Unactivated Alkenes via Migratory Insertion Processes3 Nickel-Catalyzed Three-Component Difunctionalization of Unactivated Alkenes via Radical Processes4 Conclusions and Perspectives
Keywords: nickel catalysis; difunctionalization; unactivated alkenes; migratory insertion; radical addition